2016
DOI: 10.1002/2015gl067009
|View full text |Cite
|
Sign up to set email alerts
|

Improved seasonal drought forecasts using reference evapotranspiration anomalies

Abstract: A novel contiguous United States (CONUS) wide evaluation of reference evapotranspiration (ET0; a formulation of evaporative demand) anomalies is performed using the Climate Forecast System version 2 (CFSv2) reforecast data for 1982–2009. This evaluation was motivated by recent research showing ET0 anomalies can accurately represent drought through exploitation of the complementary relationship between actual evapotranspiration and ET0. Moderate forecast skill of ET0 was found up to leads of 5 months and was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…The PET, dew point depression, and soil moisture weights are largest from lag 0 to lag +1, and all these predictors have almost no weight from past lags (−3 to −1). The fact that the peak weight is shifted toward positive lags compared to the precipitation suggests that CFS forecasts of these variables are more skillful, which is consistent with McEvoy et al ().…”
Section: Resultssupporting
confidence: 86%
“…The PET, dew point depression, and soil moisture weights are largest from lag 0 to lag +1, and all these predictors have almost no weight from past lags (−3 to −1). The fact that the peak weight is shifted toward positive lags compared to the precipitation suggests that CFS forecasts of these variables are more skillful, which is consistent with McEvoy et al ().…”
Section: Resultssupporting
confidence: 86%
“…One challenge of the climate forecast from coupled GCMs is that the precipitation forecast quickly loses skill after 2 weeks because of the inherent chaotic nature of the atmosphere (Lavers et al, ; Smith et al, ; Yuan et al, ). There are large uncertainties in the precipitation forecast, and skillful climate forecast beyond the 1 month lead is still a prevailing challenge (Mcevoy et al, ; Saha et al, ; Weisheimer et al, ; Wood et al, ; Yuan et al, ). This leads to limitations of reliable drought prediction of long lead time, especially in midlatitude (or extratropics) regions in which the climate predictability is low (Sohn & Tam, ).…”
Section: Challenges In Drought Predictionmentioning
confidence: 99%
“…For example, Hu and Willson () and Sun et al (), Sun, Chen, Ju, et al () have reported that the impact of ET 0 on drought could be equivalent to or even higher than that from precipitation. Consequently, understanding the spatial and temporal variations in ET 0 is a vital component for comprehensively understanding hydrometeorological changes and is helpful for better monitoring and predicting drought (Beguería, Vicente‐Serrano, Reig, & Latorre, ; Li, He, Quan, Liao, & Bai, ; McEvoy, Huntington, Mejia, & Hobbins, ; Sun et al, ; Sun, Chen, Sun, et al, ; Vicente‐Serrano, Beguería, & Lópezmoreno, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this provides an efficient tool to more accurately and comprehensively understand the underlying mechanisms of changed ET 0 across China. Furthermore, by considering the importance of ET 0 for the estimation of crop water demand and drought forecasting systems (McEvoy et al, 2016), obtaining detailed information about ET 0 is critical before developing countermeasures for policy makers. Large-scale atmospheric or coupled atmosphere-ocean modes of climate variability (usually referred to as teleconnections due to their long-distance range of influence) can provide a useful framework for linking ET 0 to climate fluctuations via influencing climate variables (e.g., wind speed, solar radiation, temperature, and relative humidity; Chen, Li, & Pryor, 2013;Li & Chen, 2014;Yu, Zhong, Bian, & Heilman, 2015;Zhu et al, 2017).…”
mentioning
confidence: 99%